The Role of the Cedar Hills/Lyons Sandstone Aquifer in the Dissolution of Halite Cement from Siliciclastic Sediments of the Permian Nippewalla Group in the Syracuse Basin in Western Kansas and Eastern Colorado - Timson, Glenn; Johnson, Kenneth (Midcontinent Geoscience, 2025)
The Syracuse Basin presents a rare opportunity to study a salt- and salt-cement-dissolution system over an extremely large area. Abundant geophysical well-log control spanning the salt- bearing interior sediments and their lateral salt-dissolved equivalents is available to define and characterize this salt-dissolution phenomenon. Detailed regional mapping using this abundant well-log database reveals a broad salt-cement-dissolution halo around the entire perimeter of the Syracuse Basin in Nippewalla Group siliciclastic sediments radiating outward from the central salt-preserved interior of the basin. Five areas around the perimeter of the basin were selected for detailed study to illustrate the dominant role of the Cedar Hills/Lyons Sandstone aquifer in the salt-dissolution system. The Cedar Hills/Lyons Sandstone stands out as the most prominent and regionally widespread aquifer within Permian sediments of the Syracuse Basin and surrounding region. Detailed regional subsurface mapping and cross sections presented in this paper clearly show that this high-quality confined aquifer delivered (and is still delivering) groundwater that is unsaturated with respect to sodium chloride and is responsible for this major regional phenomenon of dissolution of halite in salt-cemented siliciclastics. We will show that water unsaturated with sodium chloride encroaches on salt-bearing siliciclastic units of the Nippewalla Group in the Syracuse Basin by first invading the Cedar Hills/Lyons Sandstone, where the water is under hydrostatic pressure. Unsaturated water then is forced down into the underlying Salt Plain Formation and Harper Sandstone, dissolving interstitial salt in those formations, and may then go deeper and dissolve the Stone Corral salt. Unsaturated water in the Cedar Hills/Lyons is locally forced upward to dissolve some or all of the overlying Flowerpot salt—mainly where the overlying Y-anhydrite aquitard is absent. A preliminary semi-regional resistivity map is presented for the Cedar Hills/Lyons Sandstone aquifer. Dramatic resistivity contrasts between fresher unsaturated recharge groundwaters (with higher resistivity readings of 10 to 20+ ohm-meters) and highly saline brines (with ultra-low resistivity readings of less than 0.1 to 0.5 ohm-meters) associated with salt-dissolution events can reveal clues about modern- and paleo-hydrologic history as well as about the dissolution and flushing history of the highly saline brines created by this process. Semi-regional dissolution “halo” maps and resistivity (water-salinity) maps are herein generated by well-log studies of the Nippewalla Group evaporitic sediments in the Syracuse Basin region. Oil and gas regulatory agencies may use these maps in well permitting, plugging, and underground injection control (UIC) activities (saltwater-disposal permitting). Industry personnel can use these maps in well planning and design in the areas affected by salt and salt-cement dissolution. Additionally, oil and gas seismic surveys could benefit by consulting the regional dissolution “halo” maps to assist in avoiding seismic-velocity pitfalls that could interfere with data interpretation. Although Permian aquifers in close association with evaporitic sediments are not typically developed for domestic use because of their poor water quality, hydrologists may be interested in mapping these saline aquifers to gain an understanding of their potential to cross contaminate nearby freshwater aquifers. This is particularly true when underlying highly saline confined aquifers could discharge upward into a shallower, overlying freshwater aquifer.